Lactation Massage for Increasing Breast Milk Production in Postpartum Mothers - Katmini Katmini; Nazilatul Maulinda Sholichah (Journal for Quality in Public Health, 2020)
Background: Breast milk is the best food for babies. But breastmilk production which is little or not smooth in the first days of delivery becomes an obstacle in breastfeeding. The study conducted by Collin and a scot in Australia showed that 556 mothers gave birth as many as 29% had stopped breastfeeding their babies in the second week on the grounds that their milk was lacking. The lack of milk production causes many mothers to easily provide prelacteal foods. This prelacteal feeding causes the amount of exclusive breastfeeding to decrease. Purpose: To obtain a scientific reference source about lactation massage, which in previous studies can increase milk production in postpartum mothers. Methods: This study is a metadata analysis using a literature review that explores the benefits of massage to increase milk production. Literature sources used are journals from Pubmed, Garuda (garba rujukan digital), Doaj, Researchgate and Google Scholar. Results: With the principle of working to maximize the mechanism of prolactin and oxytocin receptors, lactation massage is a solution to overcome the smooth production of breast milk and minimize the side effects of delayed breastfeeding. In a study conducted by Aprilianti, lactation massage had a tendency to rapid onset of lactation 5.57 times greater than mothers who received oxytocin massage. Conclusion: This article tries to examine the problem of breastfeeding in postpartum mothers based on literature review. In general the role of lactation massage is successful in smoothing milk production, but there are a number of things that need to be evaluated.